2003
DOI: 10.1577/1548-8659(2003)132<0590:eopraf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Predation Risk and Foraging Return on the Diel Use of Vegetated Habitat by Two Size-Classes of Bluegills

Abstract: Little is known about nocturnal habitat selection by fishes under the risk of predation. Using a photoperiod of 15 h light : 9 h dark, we quantified the diel use of artificial macrophytes and open water by two size‐classes of bluegill Lepomis macrochirus when the open water was empty (control), contained food, or contained both a caged predator and food. Small bluegills (6.2–7.7 cm total length) spent significantly more time in macrophytes in the predator and food treatment than in the control, followed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 53 publications
2
38
1
Order By: Relevance
“…Because piscivorous fish were not present in the ponds, it was surprising that bluegill foraged so heavily in the vegetated habitat. Shoup et al (2003) found that bluegill in the laboratory spent 40-80% of their time in artificial macrophytes even in the absence of a predator and when food was only available in the open water. Either bluegill cannot accurately assess predation risk or some other mechanism causes bluegill to forage in vegetated habitat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because piscivorous fish were not present in the ponds, it was surprising that bluegill foraged so heavily in the vegetated habitat. Shoup et al (2003) found that bluegill in the laboratory spent 40-80% of their time in artificial macrophytes even in the absence of a predator and when food was only available in the open water. Either bluegill cannot accurately assess predation risk or some other mechanism causes bluegill to forage in vegetated habitat.…”
Section: Discussionmentioning
confidence: 99%
“…However, structurally complex habitats can reduce foraging return and growth rate of juvenile fishes (Persson 1991;Diehl and Eklov 1995;Shoup et al 2003). The optimal diet for juvenile bluegill (Lepomis macrochirus) is often considered to be pelagic zooplankton (Mittelbach 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetated habitats are important refuge areas against high currents and aquatic predators, particularly for small fish (e.g., Allouche, 2002;Shoup et al, 2003). For invertebrates, the pattern of greater richness may result from higher hydrodynamic disturbance in mountain rivers, (Townsend, 1989;Voelz & McArthur, 2000;Wright & Li, 2002;Willis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Crayfish have been implicated in the decline of fish populations mainly indirectly due to competition for food and shelter (Guan and Wiles 1997, Miller et al 1992, Gherardi 2002, Nyström 2002, Light 2005 and through the destruction of macrophyte beds, which are important habitats for juvenile fish (Rubin and Svensson 1993, Scheidegger and Bain 1995, Shoup et al 2003.…”
Section: Crayfish Predation On Fishmentioning
confidence: 99%